Sources for Teaching China after Mao - Mark Baker (Education About Asia, 2026)
It is now fifty years since the death of Mao Zedong in 1976; almost two-thirds of the history of the People’s Republic of China is the post-Mao era. The reform era is at the cutting edge of research in Chinese history. At least in my own institution, students with interests in international politics and economy (including many non-history majors) are keen to explore the history of China’s recent decades. But we have struggled to bridge the gap between Mao’s China and Xi Jinping’s. Many instructors feel ill-equipped to teach the history of China’s last five decades, beyond the barebones overview of high politics and economic growth as an afterthought to longer survey classes. Textbooks providing a historical framework are surprisingly thin on the ground; primary sources are scattered and online collections (usually assembled in the 2000s for teaching then-contemporary China) are often dead links. After a short introduction, this teaching resource supports high school and undergraduate instructors by providing two things: first, it identifies reliable survey texts that can offer a secure framework for teachers. Second, it suggests and provides some contextual information on short primary sources suitable for high school and undergraduate survey curricula. These include some key sources on politics, but also texts and visual material on culture, society, media and gender that can help students see recent Chinese history as a three-dimensional, human story.
Keywords: China; People' s Republic of China; PRC; Mao; Mad Zedong; Xi Jinping